2016
DOI: 10.1097/j.pain.0000000000000429
|View full text |Cite
|
Sign up to set email alerts
|

Markov chain evaluation of acute postoperative pain transition states

Abstract: Prior investigations on acute postoperative pain dynamicity have focused on daily pain assessments, and so were unable to examine intra-day variations in acute pain intensity. We analyzed 476,108 postoperative acute pain intensity ratings clinically documented on postoperative days 1 to 7 from 8,346 surgical patients using Markov Chain modeling to describe how patients are likely to transition from one pain state to another in a probabilistic fashion. The Markov Chain was found to be irreducible and positive r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 51 publications
0
12
0
Order By: Relevance
“…Additional measures capturing temporal dynamics of pain can be derived from EMA but these were not considered here because they require more specialized analyses. For example, novel applications of time-series analyses have been shown to capture unique temporal features of pain intensity, including the persistence (e.g., autocorrelation) of pain states and the amplitude of shifts between elevated and reduced pain states, which may provide important avenues for future efforts to optimize the detection of efficacious treatments [30,43,55].…”
Section: Relationships Between Changes In Pain Indices and Patient Glmentioning
confidence: 99%
“…Additional measures capturing temporal dynamics of pain can be derived from EMA but these were not considered here because they require more specialized analyses. For example, novel applications of time-series analyses have been shown to capture unique temporal features of pain intensity, including the persistence (e.g., autocorrelation) of pain states and the amplitude of shifts between elevated and reduced pain states, which may provide important avenues for future efforts to optimize the detection of efficacious treatments [30,43,55].…”
Section: Relationships Between Changes In Pain Indices and Patient Glmentioning
confidence: 99%
“…For acute pain, a natural application is tracking dynamic changes in postsurgical pain within and across days with momentary assessments, as illustrated in a recent study. 49 This study analyzed momentary pain reports of over 8000 patients, which were recorded by medical staff every 4 hours on postoperative days 1 through 7 and documented in patients' electronic medical records. Using Markov Chain modeling, they were able to predict the course of pain states during postoperative recovery.…”
Section: How Momentary Studies Can Enhance Our Understanding Of Pamentioning
confidence: 99%
“…Eleven original articles were found that reported results from 9 different projects (see Supplemental Table 1, available at http://links.lww.com/PAIN/B159 ). 6 , 7 , 9 , 15 , 19 , 28 , 38 , 42 , 49 , 55 All the studies were observational designs and most investigated pain intensity, 9 , 15 , 19 , 28 , 34 , 38 , 42 , 49 , 55 pain interference, 7 , 19 , 27 and pain behavior, 19 or examined relationships between pain and other domains (such as sleep 55 or social support 9 ). One study took a more methodological approach investigating the feasibility of promising statistical models.…”
Section: Recent Pain Ecological Momentary Assessment Studiesmentioning
confidence: 99%
“…Tighe et al used Markov decision processes to model pain transition states [9]. Intraday fluctuations and short-term analgesic response remains an open area of research, one in which machine learning may play an important role.…”
Section: Related Workmentioning
confidence: 99%